Autoestima profesional y actividad física en estudiantes de la educación física de la UNSCH - Lozano Guillen, Ruth (2022)
The physical education career has been undervalued socially, which can affect professional self-esteem. Professional self-esteem refers to a set of perceptions, feelings, thoughts, and tendencies directed towards professional practice. The aim of this study was to establish the relationship between physical activity and professional self-esteem in physical education students at UNSCH. A quantitative correlational design was employed, using the IPAQ to assess the level of physical activity and a previously validated questionnaire on professional self-esteem, which demonstrated objectivity and reliability with a Cronbach's alpha of 0.960. The sample consisted of 64 fourth-year students from the physical education program. 73.4% of students had high levels of physical activity and 76.6% had high levels of professional self-esteem. In conclusion, a low significant correlation was found between physical activity and professional self-esteem (Rho = 0.269, p=0.032, two-tailed) among the physical education students.